2020
DOI: 10.2147/jep.s236792
|View full text |Cite
|
Sign up to set email alerts
|

<p>Chemically-Modified Curcumin 2.24: A Novel Systemic Therapy for Natural Periodontitis in Dogs</p>

Abstract: Purpose:To determine the effect of a pleiotropic MMP-inhibitor, a novel chemicallymodified curcumin 2.24 (CMC2.24), on the clinical and biological measures of naturallyoccurring periodontitis in the beagle dog. Methods: Eight adult female dogs with generalized periodontitis were distributed into two groups: Placebo and Treatment (n=4/group). After a 1-hr full-mouth scaling and root planing (SRP) at time 0, placebo or CMC2.24 (10mg/kg) capsules were orally administered once/day for 3 months. Various clinical pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 55 publications
2
34
0
1
Order By: Relevance
“…Our group has reported on CMC2.24, a triketonic N -phenylaminocarbonyl derivative of bis-demethoxycurcumin, which exhibits enhanced stability and solubility compared to curcumin and has emerged as a ‘lead compound’ for several pharmacological applications such as treatment of anthrax by inhibition of the metalloprotease, lethal factor [ 21 ], treatment of cancers of the pancreas [ 22 ] and prostate [ 23 ], normalizing wound healing in diabetic rats [ 24 ], reduction in severity of periodontitis and inhibition of alveolar bone resorption associated with the disease in a rat model [ 25 , 26 ]. In addition, CMC2.24 has shown superior anti-inflammatory activity compared to the parent compound curcumin, in inhibiting periodontitis-induced bone resorption in rats via multiple mechanisms [ 27 ], and most recently, for the treatment of natural periodontitis in beagle dogs [ 28 , 29 ]. Other studies have established the pleotropic activities of CMC2.24 in inhibiting matrix metalloproteinases (MMPs) [ 30 ] and nuclear-factor kB (NF-kB), thereby reducing inflammation in models of diabetes-induced periodontitis [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has reported on CMC2.24, a triketonic N -phenylaminocarbonyl derivative of bis-demethoxycurcumin, which exhibits enhanced stability and solubility compared to curcumin and has emerged as a ‘lead compound’ for several pharmacological applications such as treatment of anthrax by inhibition of the metalloprotease, lethal factor [ 21 ], treatment of cancers of the pancreas [ 22 ] and prostate [ 23 ], normalizing wound healing in diabetic rats [ 24 ], reduction in severity of periodontitis and inhibition of alveolar bone resorption associated with the disease in a rat model [ 25 , 26 ]. In addition, CMC2.24 has shown superior anti-inflammatory activity compared to the parent compound curcumin, in inhibiting periodontitis-induced bone resorption in rats via multiple mechanisms [ 27 ], and most recently, for the treatment of natural periodontitis in beagle dogs [ 28 , 29 ]. Other studies have established the pleotropic activities of CMC2.24 in inhibiting matrix metalloproteinases (MMPs) [ 30 ] and nuclear-factor kB (NF-kB), thereby reducing inflammation in models of diabetes-induced periodontitis [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our results indicated that a short-term/1month protocol, although it did not result in obvious clinical improvement at this early stage, did appear to reduce both pro-and activated-MMP-9 in peripheral blood, which might affect the systemic environment, and also serves as an early and sensitive biomarker that precedes and predicts future clinical changes in oral (and other) inflammatory diseases. In brief, although a 1-month CMC2.24 treatment produced no detectable effect on clinical parameters temporarily, these were indeed observed with longer-term/3-momth therapy (24). At baseline (Figure 2), the levels of activated-MMP-9 in CMC2.24-treated group was 100% greater/higher (p < 0.05) than in the placebogroup.…”
Section: Discussionmentioning
confidence: 83%
“…It should be noted that the severity of clinical parameters of periodontitis was significantly reduced at the 3-month timeperiod with this regimen of HMT [p < 0.05, data already published (24)].…”
Section: Clinical Parametersmentioning
confidence: 75%
See 1 more Smart Citation
“…Seven experimental trials involving 162 rats and 8 dogs were concerned in this systematic review over 14-90 days. 10,13,[16][17][18][19][20] Five articles were published in the USA and two studies were conducted in Brazil. Besides, all studies are contemporary, as the oldest of them was published in 2014.…”
Section: General Characteristicsmentioning
confidence: 99%